Nature-inspired enhanced microscale heat transfer in macro geometry - Goh, Aik Ling (2016)
In this study, nature-inspired enhanced microscale heat transfer in macro geometry has been achieved. An annular microchannel of mean channel gap 300 µm and length 30 mm is formed by securing a cylindrical insert of mean diameter 19.4 mm within a cylindrical pipe of internal diameter 20 mm. The nature-inspired Inverted Fish Scale, Fish Scale and Durian enhancement profiles are introduced on the insert surface to improve the convective heat transfer coefficient, for a constant heat transfer area of 18.85 cm2. About 600 steady-state measurements have been collected using 22 microchannel profiles, up to 27 flow conditions (350≲Re≲4,600) for each profile using liquid-phase water, and 2 wall heat fluxes of 13.3 and 53.0 W/cm2. Working correlations have been successfully developed for the average Nusselt number and friction factor, to be used in the design of macroscale heat exchangers employing conventional fabrication techniques and yet exhibiting microchannel heat transfer capabilities.